Equipment Borrowing and Room Booking Information System at the Politeknik Statistika STIS - Hadi Nugroho, Setya; Marsisno, Waris (Politeknik Statistika STIS, 2025)
The management of goods and space lending services at the Politeknik Statistika STIS is currently still done manually, resulting in various operational constraints such as limited access to information, inefficient processes, and potential errors in recording. This impacts the quality of service and the effectiveness of campus asset utilization. This study aims to design and build a website-based goods and space lending information system to address these issues. The system developers aimed to provide users with access to information on goods and space availability, simplify the loan application process, and improve the accuracy of inventory data. The system was developed using the SDLC method with a prototyping approach, while The researchers carried out the evaluation process using Black Box Testing and a PSSUQ survey survey to measure ease of use and user satisfaction. The developers successfully built the system and confirmed through Black Box Testing that all features operate correctly, and the PSSUQ evaluation shows an average score of 1.69, indicating that this system is well received and provides a high level of satisfaction for users.